ANALISIS KRITIS AGENDA UTANG NEOLIBERAL DALAM PENDANAAN IKLIM : Studi Kasus Indonesia - Nazaruddien Agus Salim Putra Angkotasan (2023)
This paper aims to explore the relations and dynamics of a hegemony power in the global climate regime, which ultimately forced Indonesia into a climate-debt trap scheme. In writing this paper, the author uses qualitative research with data collection techniques in the form of literature studies that use secondary data as a source of data in this research. What interests the writer in examining this matter is the assistance provided by global neoliberal actors, especially developed countries, can never be refused by developing countries, even though developing countries already know that this assistance has another purpose to push developing countries into another crisis. The author uses the Coxian perspective pioneered by Robert Cox as an analytical knife in explaining the hegemony conditions in the global climate regime that force developing countries to follow the interests of developed countries.